Life beyond the home: Nutritional, occupational, social and environmental predictors of common mental disorders among Indian mothers with 6- to 23-month-old infants (P11-026-19) - Scott, Samuel P.; Arrieta, Alejandra; Kumar, Neha; Menon, Purnima; Quisumbing, Agnes R. (Oxford University Press, 2019)
The mental wellbeing of mothers with young children has been shown to positively affect child development. Little, however, is known about which factors are related to optimal maternal mental health in high poverty rural contexts where women face a broad array of challenges at multiple levels daily.